Apology Strategies Used by Prime Minister Kevin Rudd on National Apology “Stolen Generation” Speech - Rismauli Manurung; Umar Mono; Yulianus Harefa (LingPoet: Journal of Linguistics and Literary Research, 2023)
This research examines the use of apology strategies applied by Kevin Rudd in his speech of stolen generation. Kevin Rudd is an Australian former politician who was the 26th Prime Minister of Australian, serving from December 2007 to June 2010. This study is conducted to find out (1) the types of apology strategies Kevin Rudd used in his speech, and (2)the way on how apology strategies used by Kevin Rudd in his speech. This study applies descriptive qualitative method. The data were taken from the transcript of Kevin Rudd’s speech. This study uses Trosborg’s theory on apology strategies. The result of apology strategy analysis in Kevin Ruud’s speech shows that he has used the apology strategy in delivering his speech. This study reveals that there are seven categories and nine sub-categories of apology strategies on Kevin Rudd’s speech. The strategies are acknowledgement of responsibility, promise and forbearance, expressing concern for the hearer, minimizing the degree of offense, explanation or account, as well as offer of repair as the type of apology strategy which are employed. Based on Trosborg’s theory, the most dominant apology strategy used by Kevin Rudd in his speech was “expression of apology”.